Applying persuasive techniques in designing educational website: Bicycle4U website / Omar Mohamad Pauzi - Mohamad Pauzi, Omar (2012)
People always wanted others to give attention to them mostly when they are talking. While for the listener, they always wanted to listen to something that is interesting and attracting. Thus, one technique of communication to make everybody pay attention to the speaker is by using Persuasive Technique either by verbal or gesture that depends on the respond of the audience. While in website, these two things are impossible to be done because machine does not have emotions. A lot of researches on implementing persuasive technique have been done on the website but mostly on the e-commerce website to attract buyers. This study focuses on identifying the elements of persuasive techniques that can be applied into an educational website and designs a prototype website to show the example for some of the persuasive technique's elements. This prototype website is named as Bicycle4U and it teach the users about bicycles including calculating the right bicycle for the users. Method used is observation of the current educational website that is related with bicycle and interview with the potential user and Human-Computer Interaction expert to design the prototype website while implementing the persuasive technique's elements. This research focuses on only four elements which are the elements of Reduction, Tailoring, Suggestion and Tunneling. This research will give more understanding about the elements of persuasive techniques because it is not giving out the theory of the mentioned elements but also the application of it in the Bicycle4U website. At the end of this research, some recommendations are given for the future works in the persuasive technique's elements in order to ensure that this research can be enhanced to the next level.